2014
DOI: 10.1890/13-1799.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐mediated biotic interactions influence enemy release of nonnative species in warming environments

Abstract: "Enemy release" occurs when invading species suffer from interactions with pathogens, parasites, herbivores, or predators to a lesser degree than native species due to a lack of shared evolutionary history. Here we provide strong support for the hypothesis that variable thermal sensitivities between a consumer and its resources can generate temperature-dependent enemy release using both a mathematical model and a field experiment. We identify three common scenarios where changes in temperature should alter ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 69 publications
1
44
0
2
Order By: Relevance
“…Whereas climate change is expected to intensify the ecological impacts of many nonnative species (Rahel and Olden 2008, Fey and Herren 2014, Lawrence et al 2014, we expect warming trends to diminish the resource competitive impacts of Mysis in many lakes due to its relatively low thermal optimum. Whereas climate change is expected to intensify the ecological impacts of many nonnative species (Rahel and Olden 2008, Fey and Herren 2014, Lawrence et al 2014, we expect warming trends to diminish the resource competitive impacts of Mysis in many lakes due to its relatively low thermal optimum.…”
Section: Implications For Fisheries Management and Invasion Ecology Imentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas climate change is expected to intensify the ecological impacts of many nonnative species (Rahel and Olden 2008, Fey and Herren 2014, Lawrence et al 2014, we expect warming trends to diminish the resource competitive impacts of Mysis in many lakes due to its relatively low thermal optimum. Whereas climate change is expected to intensify the ecological impacts of many nonnative species (Rahel and Olden 2008, Fey and Herren 2014, Lawrence et al 2014, we expect warming trends to diminish the resource competitive impacts of Mysis in many lakes due to its relatively low thermal optimum.…”
Section: Implications For Fisheries Management and Invasion Ecology Imentioning
confidence: 99%
“…For example, changes in temperature can alter trophic dynamics through asymmetric shifts in the production and consumption rates of ectothermic species (Taniguchi et al 1998, Rahel and Olden 2008, Fey and Herren 2014). For example, changes in temperature can alter trophic dynamics through asymmetric shifts in the production and consumption rates of ectothermic species (Taniguchi et al 1998, Rahel and Olden 2008, Fey and Herren 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58]). For populations in highly seasonal environments, reproduction and death occur in pulses, the timing and intensity of which are controlled by temperature.…”
Section: (D) Temperature and Consumer -Resource Dynamicsmentioning
confidence: 99%
“…Studies have also linked altered temperature to the movement (Walther et al, ), establishment success (Chown et al, ), and spread (Stachowicz, Terwin, Whitlatch, & Osman, ) of species beyond their natural ranges. Recently, variation in temperature has been shown to influence competition, insect–plant, and predator–prey interactions involving native and exotic species (Fey & Cottingham, ; Fey & Herren, ; Lu, Siemann, Shao, Wei, & Ding, ). For example, Fey and Herren () found that increasing temperature disproportionately benefited an exotic species compared to a native congener under threat from a shared native predator, resulting in a temperature‐dependent enemy release.…”
Section: Introductionmentioning
confidence: 99%